Cutaneous changes in obese patients before and after bariatric surgery - Bundela, Manjari; Bhatia, Kailash; Bhandari, Mohit; Namdeo, Chaitanya; Gupta, Swati (International Journal of Research in Dermatology, 2023)
Background: Obesity being a multi-organ disease also affects the skin. Bariatric surgery results in the improvement or remission of many obesity-related comorbid conditions, as well as sustained weight loss and improvement in quality of life. After bariatric surgery, both positive and negative impacts on the skin are seen. Studies have reported improvement in many skin conditions. The present study was conducted with the aim to find cutaneous changes in obese patients before and after bariatric surgery were assessed. Methods: This prospective, observational study included 61 obese subjects who had undergone bariatric surgery. clinical findings of skin, nails, and hair before and after bariatric surgery at 3 months, 6 months, and 9 months follow-up were also recorded. Results: Mean age of the subjects was 44.4±13.284 years. Bariatric surgery resulted in a significant decrease in BMI [40.3 (38.25-42.70) vs 32.0 (30-35) kg/m2]. The median of % effective BMI change was 20.46% (17.12%-24.66%) kg/m2. Amongst obese subjects, the most frequently seen skin condition was acanthosis nigricans [17 (27.9%)] followed by acrochordon [15 (24.6%)] and intertrigo [10 (16.4%)]. Our study showed no significant difference in the prevalence of various skin conditions/diseases before and after the bariatric surgery except for intertrigo, tinea corporis, and striae rubra. Conclusions: various skin/hair/nail conditions and/or diseases develop amongst obese individuals, acanthosis nigricans, acrochordon, intertrigo, seborrheic dermatitis, chronic telogen effluvium, onychomycosis, and longitudinal ridges are common. Weight loss after bariatric surgery provided improvement in skin conditions/diseases.